2014
DOI: 10.1115/1.4026320
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Effects on Stress Wave Propagation

Abstract: The present study, through finite element simulations, shows the geometric effects of a bioinspired solid on pressure and impulse mitigation for an elastic, plastic, and viscoelastic material. Because of the bioinspired geometries, stress wave mitigation became apparent in a nonintuitive manner such that potential real-world applications in human protective gear designs are realizable. In nature, there are several toroidal designs that are employed for mitigating stress waves; examples include the hyoid bone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The impact surface of the horn sheath is wide and thick seen from the cross section. The tapered and spiral horn sheath can attenuate the shocks to protect the skull and brain from reflection (Johnson et al, ). The inner core is hollow and contains multiple compartments which have the characteristics of lightness and stable mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The impact surface of the horn sheath is wide and thick seen from the cross section. The tapered and spiral horn sheath can attenuate the shocks to protect the skull and brain from reflection (Johnson et al, ). The inner core is hollow and contains multiple compartments which have the characteristics of lightness and stable mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…But the presence of voids on the side portions allows for some movement. At the same time, the irregular geometry allows for multiple reflection of stress waves within the specimens, similar to the phenomenon observed in the hyoid structure of a woodpecker's head [35]. This is not possible in the reference model, which provides a smooth, straight path for the propagation of any stress waves that are generated during the dynamic impact event.…”
Section: Bulk Modelsmentioning
confidence: 95%
“…It was previously suggested that horn tip oscillations intentionally directed into side-to-side (medial-lateral) motion may be one mechanism of energy dissipation. Additionally, geometry has been shown to affect dynamic wave propagation in other curved structures (Johnson et al, 2014). For example, the woodpecker's curved hyoid bone absorbs impact energy during pecking and has been used for bioinspired design of impact mitigation structures (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%